Understanding And Implementation Of The Concept Of Natural Disaster Mitigation Materials In Geography Learning At Man 2 Palu City - Nurhaedah, Nurhaedah; Misnah; Alif Yunar; Zefitni (Kirana Publisher (KNPub), 2023)
Natural disasters can occur in a way suddenly or through an ongoing process in a way slowly. Disaster Of course can give rise to impact loss from various aspects, then required understanding to the public from an early age through education in schools/madrasas about types of disasters and their mitigation To minimize the impact caused. Teachers have an important role to provide learning about disasters and mitigating natural disasters. Objective 1. How students understand about draft material mitigation disaster nature in the eyes lesson geography at MAN 2 Palu City, 2. How teachers implement it learning about material mitigation disaster nature in the eyes lesson geography at MAN 2 Palu City. Sample viz student class XI IPS with total 53, one eye teacher lesson geography as informant . Type of research This is a descriptive survey. Data collection techniques through questionnaires , interviews and documentation . Research results showing students' understanding on indicator 1. Types and Characteristics Natural Disaster, obtained percentage an average score of 76% with category good; 2. Understand Cycle Countermeasures Disaster, obtained an average score of 63% with category good ; 3. Analyze Distribution of Areas Prone to Natural Disasters in Indonesia, obtained an average score of 76% with category good ; 4. Identifying Institutions That Play a Role in Countermeasures Natural Disasters, with an average score of 63% is in the category good; 5. Explain Community Participation in Mitigation of Natural Disasters in Indonesia with an average score of 66% is in the good category. Percentage average value _ overall 72.3%, with study results showing students' understanding about draft material mitigation disaster nature in the eyes lesson geography at MAN 2 Palu City is in the category good .